I want to calculate $\int_{\mathbb R^3} \exp(-x^tAx + b^tx) \,\lambda_3(dx)$ for $$A= \begin{pmatrix} 2 & -1 & 0 \\ -1 & 2 & 1 \\ 0 & 1 & 1\end{pmatrix}, \quad b= \begin{pmatrix} 1 \\ 2 \\ 3\end{pmatrix}$$ I would like to ask if my solution is correct and if there is a faster/better way.

We see that $A$ is a positive definite symmetric covariance matrix.

Call $B := 2A$ and write $$-x^tAx + b^t x = -\frac{1}{2}(x^tBx - 2b^tx) = -\frac{1}{2}\left((x-B^{-1}b)^t B(x-B^{-1}b) -b^tB^{-1}b\right)$$ so we get $$\int_{\mathbb R^3} \exp(-x^tAx + b^tx) \,\lambda_3(dx) = \exp(b^tA^{-1}b) \int_{\mathbb R^3} \exp\left(-\frac{1}{2}\left((x-B^{-1}b)^t B(x-B^{-1}b)\right)\right) \,\lambda_3(dx) $$ Now the integral is the integral over the $3$-dimensional centered normal distribution and evaluates to $$\int_{\mathbb R^3} \exp\left(-\frac{1}{2}\left((x-B^{-1}b)^t B(x-B^{-1}b)\right)\right) \,\lambda_3(dx) = (2\pi)^{3/2}\det B = (8\pi)^{3/2} \det A$$ So it now only remains to compute $\det A$ and $A^{-1}$: $$\det A = 1, \quad A^{-1} = \begin{pmatrix} 1 & 1 & -1 \\ 1 & 2 & -2 \\ -1 & -2 & 3\end{pmatrix}$$ hence $$\int_{\mathbb R^3} \exp(-x^tAx + b^tx) \,\lambda_3(dx) = \exp(b^t A b) (8\pi)^{3/2} = e^{10} (8\pi)^{3/2}.$$


According to my calculations the integral has the value $e^{5/2}\pi^{3/2}$. I give two different answers. It is a matter of taste which one is the faster/better one.

Answer 1. This is essentially your solution. I omit the matrix $B$. Since \begin{equation*} -\left(x-\dfrac{1}{2}A^{-1}b\right)^{t}A\underbrace{\left(x-\dfrac{1}{2}A^{-1}b\right)}_{=y} + \dfrac{1}{4}x^tA^{-1}x = -y^{t}Ay +\dfrac{1}{4}x^tA^{-1}x . \end{equation*} I get \begin{equation*} I = \int_{\mathbb{R}^3}\exp(-x^{t}Ax+b^{t}x )\,\mathrm{d}x_{1}\mathrm{d}x_{2}\mathrm{d}x_{3} = \exp(\dfrac{1}{4}x^tA^{-1}x)\int_{\mathbb{R}^3}\exp(-y^{t}Ay)\,\mathrm{d}y_{1}\mathrm{d}y_{2}\mathrm{d}y_{3} \end{equation*} The next substitution is $y = Qz$ where $Q$ is an orthogonal matrix with columns that are orthonormal eigenvectors to $A$. Then $\det Q = 1$ and \begin{equation*} y^{t}Ay =\lambda_{1}z_{1}^{2}+\lambda_{1}z_{2}^{2}+\lambda_{1}z_{3}^{2} \end{equation*} where $\lambda_{k}, k=1,2,3$, are positive eigenvalues to $A$. Now we return to the integral \begin{gather*} I = \exp(\frac{1}{4}10)\int_{\mathbb{R}^3}\exp(-\lambda_{1}z_{1}^{2}-\lambda_{2}z_{2}^{2}-\lambda_{3}z_{3}^{2})\,\mathrm{d}z_{1}\mathrm{d}z_{2}\mathrm{d}z_{3} =\\[2ex] e^{5/2}\dfrac{\pi^{3/2}}{\sqrt{\lambda_{1}\lambda_{2}\lambda_{3}}} = e^{5/2}\dfrac{\pi^{3/2}}{\sqrt{\det(A)}} = e^{3/2}\pi^{3/2} \end{gather*} where I have used that $\lambda_{1}\lambda_{2}\lambda_{3}=\det(A) = 1.$

Answer 2. In this solution completing the square is essential. Put $x^t = \left(x_1\, x_2\, x_3\right)$. Then \begin{equation*} -x^{t}Ax+b^{t}x = -2x_1^2+2x_1x_2-2x_2^2-2x_2x_3-x_3^2+x_1+2x_2+3x_3 = -2u_1^2-\dfrac{3}{2}u_2^2-\frac{1}{3}u_3^2 +\dfrac{5}{2} \end{equation*} where \begin{equation*} \left\{\begin{array}{lclclclcl} u_1&=&x_1&-&\dfrac{1}{2}x_2&&&-&\dfrac{1}{4}\\[2ex] u_2&=&&&x_2&+&\dfrac{2}{3}x_3&-&\dfrac{5}{6}\\[2ex] u_3&=&&&&&x_3&-&2 \end{array}\right. \end{equation*} With notation from answer 1 I get \begin{equation*} I =e^{5/2}\int_{\mathbb{R}^3}\exp\left(-2u_1^2-\dfrac{3}{2}u_2^2-\frac{1}{3}u_3^2\right)\,\mathrm{d}u_{1}\mathrm{d}u_{2}\mathrm{d}u_{3} = e^{5/2}\dfrac{\sqrt{\pi}}{\sqrt{2}}\dfrac{\sqrt{\pi}}{\sqrt{3/2}}\dfrac{\sqrt{\pi}}{\sqrt{1/3}} = e^{3/2}\pi^{3/2} . \end{equation*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.